What You See Is What You Get: Science Images on the Web. - Kristine M. Alpi (Issues in Science and Technology Librarianship)
A selection of image-rich web sites in a variety of scientific disciplines is offered as a starting point for reference questions and educational programs. Tools for keeping up with new image resources are introduced. This review does not cover searching general World Wide Web sites or general commercial image databases for science images.